2017
DOI: 10.3126/kumj.v13i3.16815
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Musculoskeletal Disorders among Registered Nurses: Evidence from the Thai Nurse Cohort Study

Abstract: BackgroundHealth, safety, and well being have been known to be influenced by occupational characteristics. Nurses constantly encounter musculoskeletal disorders (MSDs) from work demands worldwide. Nevertheless, there is insufficient of knowledge regarding causes of musculoskeletal disorders among nurses in Thailand. ObjectiveTo investigate factors associated with musculoskeletal disorder among registered nurses in Thailand. MethodThis study is part of the 2009 Thai Nurse Cohort Study which consisted of 18,756 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
5
7
0
1
Order By: Relevance
“…It is important to offer early intervention to treat anxiety among nurses to prevent musculoskeletal disorders. Numerous studies have identified relevant factors similar to the results of our study: female gender [ 41 , 48 ], absenteeism [ 9 ], and psychosocial factors [ 8 , 12 , 16 , 31 , 32 , 34 , 35 , 39 , 42 , 48 51 ]. In Vietnam, a previous study in Haiphong in Vietiep hospital (which have the largest number of nurses) also illustrated some factors as the gender, stress, and high age associated with MSDs [ 19 ], which was similar to our study outcomes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is important to offer early intervention to treat anxiety among nurses to prevent musculoskeletal disorders. Numerous studies have identified relevant factors similar to the results of our study: female gender [ 41 , 48 ], absenteeism [ 9 ], and psychosocial factors [ 8 , 12 , 16 , 31 , 32 , 34 , 35 , 39 , 42 , 48 51 ]. In Vietnam, a previous study in Haiphong in Vietiep hospital (which have the largest number of nurses) also illustrated some factors as the gender, stress, and high age associated with MSDs [ 19 ], which was similar to our study outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…However, this result was lower than those observed in Uganda in 2013 among 755 nurses (80,8%) [ 13 ], in Estonia (84%) [ 31 ], 89% in Portugal [ 9 ], in Macedonia (85%) [ 10 ], and 80.8% in Uganda [ 13 ] and, in our Asia, there were Saudi Arabia (85%) [ 15 ], Iran (88%) [ 16 ], and Japan (85.5%) [ 32 ]. On the contrary, this prevalence was higher than that in France (from 10% to 50%) [ 8 ], in USA (from 35.1% to 47%) [ 11 ], and (from 32.8% to 57.1%) in Brazil [ 12 ]; in Pakistan (31.6%) [ 33 ], in Thailand (47.8%) [ 34 ], and in Malaysia (from 35.3% to 48.9%) [ 35 ]. There were possibly two reasons for these differences: firstly, it depends on the nursing work condition and characteristics of each continent, each country, and each region; secondary, a higher frequency is contributed by the number of symptoms of MSDs which appears in the assessment questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity related genitourinary system conditions include urinary incontinence due to weakened pelvic muscles and abnormal ovulation. 42 …”
Section: Impactmentioning
confidence: 99%
“…Furthermore, it is well documented that prolonged recovery from work-related, work-limiting injuries is more common as workers age (Delloiacono, 2016). While occupational risks associated with illness and injury among nurses are varied, occupational stress, patient handling, and shift work are noted as major contributors (Gomaa et al, 2015;Stimpfel et al, 2015;Thinkkhamrop & Laohasiriwong, 2015;Wallis, 2015). There is also evidence to suggest that 44% of all reported musculoskeletal injuries are attributed to overexertion and patient interaction (Gomaa et al, 2015;Wallis, 2015).…”
Section: Occupational Health Considerations For Aging Nursesmentioning
confidence: 99%